Comparative analysis of small and medium sized enterprises in the process of Turkish integration to the economic structure of European Union: SMSEs in Turkey and Germany - Demirci, Cengiz (My University, 2000)
unknown
Keywords: Avrupa Topluluğu_Türkiye; Küçük Ve Orta Işletmeler